New information on the skipper fauna of Guangxi, China (Lepidoptera, Hesperiidae) - Xue, Guoxi; Niu, Jinqiao; Long, Jifeng; Zeng, Weibo (Zootaxa, 2018)
The skipper fauna of Guangxi is updated based upon field surveys and examinations of specimens. Two genera and 16 species/subspecies are recognized as new records to Guangxi, of which one genus and four species are recorded from China for the first time. Distribution of seven species/subspecies in Guangxi are confirmed as well. The females of four species are described for the first time. The male genitalia of three species are illustrated and re-described. Taxonomic notes on some of these species are provided.